Semana Santa de Ávila: patrimonio y turismo - Cátedra, María (Trabalhos de Antropologia e Etnologia, 2020)
This essay refers to the Holy Week in Ávila, trying to analyse the touristic and patrimonial impact of these celebrations from two periods: the first years of its development (1988-9) and the present (2017). Through the processions and brotherhoods of the first stage emerge various groups (children, youth, women and men) social classes (guilds, occupations, social stratification) and neighbourhoods (centre and periphery). However, 30 years later, new organizations have appeared that reflect changes in the city and its collectives, ideological changes and changes in the consideration of ritual itself. But fundamentally it is appreciated a strong tourist implication and a contextualization very marked by its imposing medieval walls. The processions symbolically reproduce the city, reaffirm it and signify it at a certain moment. The analysis of Holy Week illuminates what the city is and how it wants to be considered.